THEORETICAL FRAMEWORK FOR THE STUDY OF LOCALLY PRODUCED TRANSMISSION OILS FOR TRUCKS OPERATING IN MOUNTAIN CONDITIONS AND HOT CLIMATIC CONDITIONS. (Conferencea, 2022)
This article analyzes the properties, quality, reliability of essential oils and the changes in the quality of oils for high temperature, dust particles.